Analysing Different Risk Management Approaches and Their Effectiveness in Enhancing Supply Chain Resilience - Hajarath, Krishna; Vummadi, Jayapal (International Journal of Supply Chain Management, 2024)
Purpose: This paper aims to review various risk management strategies as well as measure its capability as an instrument to strengthen the chain resilience in the backdrop of the present-day economic environment. Methodology: The paper utilizes well-known literature review techniques to gather and analyze the strategies including diversification, collaboration, technology adoption, and contingency planning that not only avoid supply chain risks but also create resiliency in organizations. It is focused on the root causes, effects, and aftermath of supply chain disruptions; the potential solutions to counter these problems are also evaluation by this process. Findings: The study points out that the traditional risk management approaches are not enough, and suggests implementing the techniques such as mapping of the supply chain, supplier diversification and investment in digital technologies like block chain, cloud computing and cyber security. These approaches aid in boosting the supply chain resilience by providing transparency, enabling backup inventory management, and improving collaboration and efficiency within the supply chain operations. Unique Contribution to Theory, Practice and Policy: The study complements the existing body of knowledge by offering a detailed overview of risk management strategies that can be implemented for the purpose of supply chain resilience. It provides with concrete suggestions on issues of diversity, the use of new technologies, and of coordination to strengthen the chains of supply against disruptions. Furthermore, the research calls for policy intervention to enable the utilization of the above-discussed strategies and increase supply chain resilience at a broader level as well.